Macroeconomic linkages and international shock transmissions in East-Asia: a global vector autoregressive approach - Hassan, Ibrahim Bakari; Mohamed, Azali; Lee, Chin; Wan Ngah, Wan Azman Saini (Taylor and Francis, 2017)
The growing interdependency among East Asian countries means that there is concern not only on the way their macroeconomic variables are linked across borders, but also on the way shocks are transmitted as a consequence. This paper investigates the effect of macroeconomic linkages on international shock transmissions in selected East Asian countries. Global Vector Autoregressive model (GVAR) is used on the quarterly data of real output, inflation, equity prices, exchange rates, and short-term interest rate over the period 1979Q2–2013Q1. The result generally shows that the focus countries are more linked to global economy through equity markets, real output, and exchange rates, signifying more tendencies for contagion effects in the same way. On the other hand, result from the dynamic analysis, shows that China contributes highest shock transmission in the real sector, whereas US is the highest in the equity market. For the exchange rate; within-regional shock transmission is found to be highest. The dominance of China in the real sector implies the possibility of business cycle synchronization in the region, especially if China is triggered; however, the insignificance currency-shock transmission between China and the rest of the East Asian countries contradicts one important criterion for optimum currency area. This means that China could vanguard the economic regionalism if its currency market is more developed and liberalized. More still, the dominance of US in capital market and second to China in the real sector explained the strategic importance of US in the global economy.